An investigation of challenges experienced by Physical Sciences novice teachers when teaching Electric circuits in Grade 10 science classrooms: A case of Johannesburg North District schools - Nkuna, Hlayisani Tracy (University of the Witwatersrand, Johannesburg, 2023)
The National Senior Certificate (NSC) diagnostic reports over the years have shown that learners perform poorly in electric circuits in the Grade 12 Physical sciences final examinations. This has raised concerns to identify the underlying reasons behind this. The learners’ performance is often linked to the teachers’ content knowledge and pedagogical knowledge. This study sought to understand the challenges that physical sciences novice teachers experience when teaching electric circuits in Grade 10 as well as the factors that contribute to these challenges. In understanding the challenges experienced by the novice teachers, this study was underpinned by Bhaskar’s (1978) theory on Critical Realism as a theoretical framework to reveal the teachers’ challenges in relation to their content and pedagogical knowledge. In conjunction to this, the study was guided by Archers’ (1995) constructs of the Social Realist Theory. The two theoretical frameworks were used to analyse the data, using stratified levels of reality from critical realism and analytical dualism from the social realist theory as an analytical tool. Employed in this study was the qualitative case study research design. The data was collected through twenty online questionnaires and five individual online semi-structured interviews with physical sciences novice teachers from the schools in the Johannesburg North district. These instruments were used to provide an in-depth account of the challenges experienced by the novice teachers and their contributing factors. The study found that the novice teachers experienced challenges with the lack of specialized resources such as fully functional laboratories and content related challenges, such as misconceptions, gate-keeping concepts and teacher centred approaches. The findings also revealed that despite being technologically oriented themselves. The findings also revealed that the novice teachers experienced challenges with the use of ICT in their teaching of electric circuits, owing to a variety of reasons related to the context of the school, their pre-service training as well as general beliefs about ICT. The study recommends that teacher training programmes should perhaps look into firstly, teaching the pre-service teachers more on how to improvise, given that most schools lack resources and secondly, the methodology courses need to consider focusing on how to equip the teachers with the correct conceptions of the main concepts of electric circuits in order to minimise the misconception perpetuated by the novice teachers as well as build they confidence in the instruction of electric circuits. The rationale for this study was on the grounds that there is not much physical science education research clearly accounting for the challenges experienced by the novice teachers post the millennial generation and the COVID-19 pandemic. This study provides ground for other researchers to explore the nature of science teaching with this current generation (generation Z). The findings from the research study reveal that the current generation experience challenges beyond content knowledge, such as a short attention span. In light of this finding, this study suggests that future research should be aimed at incorporating the technological aspect of teaching in science topics in order to make the science topics interesting and relevant to the learners.
A research project submitted to the Faculty of Humanities, in fulfilment of the requirement for the degree of Masters in Education, Wits School of Education, University of the Witwatersrand, Johannesburg, 2023.
Keywords: Novice teacher; Content knowledge; Pedagogical knowledge; Information Communication Technology (ICT); Generation Z; Critical realism; Social Realist Theory; UCTD; SDG-4: Quality education